Assessing radiation exposure during endoscopic-guided percutaneous nephrolithotomy - Lantz, Andrea G; O’Malley, Padraic; Ordon, Michael; Lee, Jason Y (Canadian Urological Association Journal, 2014)
Introduction: Percutaneous nephrolithotomy (PCNL) may be associated with significant ionizing radiation exposure for patients and operating room staff. Endoscopic-guided PCNL (ePCNL) is a technique that may be associated with less radiation exposure. This study examines ePCNL-related radiation exposure (fluoroscopytime, effective dose) and investigates variables that may predict increased exposure. Methods: A retrospective review of all consecutive ePCNLs performed at our institution, by a single surgeon, was conducted between November 2011 and November 2013. Patient demographics, stone characteristics and perioperative details were recorded, including radiation exposure. Pearson and Spearman correlation were used to assess variables correlated with radiation exposure. Results: In total, 55 ePCNL cases were included in the study. The mean age was 60 ± 15 years, mean body mass index (BMI) 30.0 ± 6.4 kg/m2 and mean stone size 3.2 × 2.1 cm. Seven cases (13%) involved complete staghorn stones, and 69% involved supracostal punctures. The mean fluoroscopy time was 3.4 ± 2.3 minutes, mean ED 2.4 ± 1.9 mSv. The treatment success rate, assessed 1-week postoperatively, was 87.3% and 7.3% of cases required ancillary procedures. The overall complication rate was 29%, but only 3 cases (5.5%) were Clavien ≥3. Longer fluoroscopy time correlated with increased stone size (p < 0.01), longer operative time (p < 0.01) and lower treatment success rates (p < 0.01); higher effective dose correlated with longer fluoroscopy time (p < 0.01) and increased skin-to-stone distance (p < 0.01). BMI did not correlate with fluoroscopy time or effective dose. Conclusions: Outcomes of ePCNL are comparable to traditional PCNL techniques and may be associated with lower radiation exposure, particularly beneficial for patients with higher BMI.